(untitled) (Altruism: The Indonesian Journal of Community Engagement, 2024)
Weddings should be a happy moment. However, in reality conflict cannot be avoided, from the lightest level to the point where it can trigger divorce. To avoid this, pre-marital guidance or courses for prospective brides and grooms are needed so that the prospective bride and groom have the provisions to face household problems until a happy married life is achieved. The aim of this research is to review the implementation of pre-marital guidance or bride and groom courses at the KUA Kraton Yogyakarta District. This research uses descriptive qualitative field research. Data was collected through observation, interviews and documentation using observation guide instruments and interview guidelines. Data is processed by data reduction, data presentation, and drawing conclusions. Based on the research results, it was found that the implementation of pre-marital guidance or courses for brides and grooms did not meet the standard syllabus for the Course Program training course published by the Director General of Islamic Community Guidance in 2013 which had been determined by the government. Pernikahan seharusnya menjadi momen yang membahagiakan. Namun, pada kenyataannya konflik tidak dapat dihindari, dari tingkat yang paling ringan hingga dapat memicu perceraian. Untuk menghindari hal tersebut, maka diperlukan bimbingan pranikah atau kursus calon pengantin agar calon pengantin memiliki bekal untuk menghadapi masalah-masalah rumah tangga hingga tercapailah kehidupan rumah tangga yang bahagia. Tujuan dari penelitian ini adalah untuk meninjau pelaksanaan bimbingan pranikah atau kursus calon pengantin di KUA Kecamatan Kraton Yogyakarta. Penelitian ini menggunakan jenis penelitian (field research) kualitatif deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dengan instrumen pedoman observasi dan pedoman wawancara. Data diolah dengan reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil penelitian yang diperoleh bahwa pelaksanaan bimbingan pranikah atau kursus calon pengantin belum memenuhi standar silabus mata diklat Program Kursus yang diterbitkan oleh Direktur Jenderal Bimbingan Masyarakat Islam tahun 2013 yang sudah ditetapkan oleh pemerintah.